Uji pemberian pupuk organik greenstar dan pupuk NPK terhadap pertumbuhan dan hasil tanaman jagung (zea mays L.): uji pemberian pupuk organik greenstar dan pupuk NPK terhadap pertumbuhan dan hasil tanaman jagung (zea mays L.) - Maria Erviana Klau; Priyono Priyono; Siswadi Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
This istudy iwas ithe iTest iof iGreenstar iOrganic iFertilizer iand iNPK iFertilizer ion ithe iGrowth iand iYield iof iCorn i(Zea imays iL), iexamine ithe iinteraction iof iGreenstar ifertilizer iand iNPK ifertilizer idosage ion ithe igrowth iand iyield iof icorn i(Zea imays iL), on iApril i29, i2021, ito iAugust i5, i2021, iin iLaen iHas, iRabasa iBiris iVillage, iWaewiku iDistrict, iMalacca iRegency, iEast iNusa iTenggara, iwith ian ialtitude iof i269 imeters iabove isea ilevel iwith iRegosol isoil itype. iThe imethod iused iwas ia icompletely irandomized idesign imethod iand ithere iwere iseveral ilevels ior iarrangements ibased ion ifactorial, iwhich iwas i16 itreatments. iEach itreatment iwas irepeated i3 itimes. iThe ifertilizers iused iwere iGreenstar ifertilizer iand iNPK ifertilizer. iBased ion ithe iresults, iit iwas ianalyzed iusing ithe Duncan iMultiple iRange iTest iat ia ilevel iof i5%. iThe iindicators ithat ibecame ithe icenter iof iattention iincluded ithe iheight iof ithe iplants, inumber iof ileaves, ileaves iarea, ilength iof ithe icob, ithe idiameter iof ithe icob, ithe iweight iof ithe icob, idry ishells, iand idry ishell iweight iper iplot. iThe iresults ishowed ithatifertilizer i(G) iand iNPK ifertilizer i(P) ihave ia ivery isignificant ieffect ion iplant igrowth iand iyield iof icorn iplants.